INTEGRATION OF ROBOTICS DESIGN INTO THE LEARNING PROCESS AT SCHOOL - KOZHAGUL, Aidos; BIDAIBEKOV, Yessen; BOSTANOV, Bektas; PAK, Nikolay; KOZHAGULOVA, Zhanar (Tchê química, 2020)
The application of teaching methods to the learning process at school is defined by the fact that every teacher or curriculum developer strives to ensure that his or her concepts of teaching and formation of the educational principles are implemented in the educational environment most effectively. Such forms of interaction cause the fact that every teacher strives to integrate the practical elements of the subject area into the learning process both as the exact structures and as the formalized complicated forms of didactics. This study aimed the revealing of this aspect of the pedagogical problem. The analysis of the previous knowledge and abilities shows that teaching the methods for the design of the robotics’ elements to the senior school students has a significant potential for the active form of the subject competencies. The obtained results of the teaching experiment have generally proved the hypothesis of pedagogical research. If to apply a unique system of didactic conditions, forms and development methods of the senior school students’ robotics design skills to robotic design and solution of tasks and practical assignments based on the construction and research of the sequence of sub-models, then it will contribute to the increase in the effectiveness of the robotic design teaching, the formation of the students’ ideas of the model nature of cognition, and the development of their cognitive and creative abilities. The obtained results show that teaching course ‘Robotics Design as a Method for Solution of Application Tasks’ to students contributes to the increase in the level of the senior school students’ robotics design skills by each particular criteria, which proves the pedagogical rationale of introducing the revealed and theoretically substantiated didactic conditions for the development of the senior school students’ robotics design skills.